Globalization, institutional quality, economic growth and CO2 emission in OECD countries: An analysis with GMM and quantile regression - Fatima, Nudrat; Zheng, Yanting; Guohua, Ni (Frontiers in Environmental Science, 2022)
This research used the dynamic panel model and QR (Quantile Regression) to examine the effect of globalization (GB), Institutional Quality (IQ), Economic Growth (EG), Electricity Consumption (EC), and Renewable Energy (RE) consumption on Carbon dioxide (CO2) emission from 1991 to 2018 in thirty-six (OCED) countries. Panel unit root tests have been employed to examine the stationarity of the study variables; the results, which included the Harris and Tzavalis (Journal of econometrics, 1999, 91 (2), 201–226) and Levin et al. (Journal of Econometrics, 2002, 108 (1), 1–24) tests, indicate that all of the variables used are a combination of I (0) and I(I). Cointegration in the study variables has been examined using the cointegration tests devised by Westerlund, Kao, and Pedroni; the results suggest that cointegration exists in the research variables. Findings of the one-step difference GMM, One-step system GMM and two-step system GMM reveal that RE consumption, GB, and IQ negatively affect the CO2 emission in (selected OECD) countries that help to reduce CO2 excretion. In contrast, EC consumption and EG become responsible for the climatic and environmental loss. Further, this study checked the robustness by using SQR (Simultaneous quantile regression) and PQR (Panel Quantile Regression). The evaluated study findings of QR (Quantile Regression) reveal that RE consumption, GB, and IQ help to reduce the CO2 emission while EG and EC consumption becomes responsible for the climatic and environmental loss. Further recommendations are suggested based on the findings.